If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 7 = 4 + -1(9x + -5) Reorder the terms: 7 + 6x = 4 + -1(9x + -5) Reorder the terms: 7 + 6x = 4 + -1(-5 + 9x) 7 + 6x = 4 + (-5 * -1 + 9x * -1) 7 + 6x = 4 + (5 + -9x) Combine like terms: 4 + 5 = 9 7 + 6x = 9 + -9x Solving 7 + 6x = 9 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 7 + 6x + 9x = 9 + -9x + 9x Combine like terms: 6x + 9x = 15x 7 + 15x = 9 + -9x + 9x Combine like terms: -9x + 9x = 0 7 + 15x = 9 + 0 7 + 15x = 9 Add '-7' to each side of the equation. 7 + -7 + 15x = 9 + -7 Combine like terms: 7 + -7 = 0 0 + 15x = 9 + -7 15x = 9 + -7 Combine like terms: 9 + -7 = 2 15x = 2 Divide each side by '15'. x = 0.1333333333 Simplifying x = 0.1333333333
| 2(x-3)+2=-2 | | (4x-2)(3x+5)= | | -4w=16 | | 228=2(2w-9)+2w | | 3(4x+2)=19 | | 5(x+4)-3x=14 | | 236=2(2w-2)+2w | | 456=2(4w-7)+2w | | (-108)+n=9 | | n+72=-288 | | 28/x=7/6 | | 456=2(7-4w)+2w | | 456=7-4w+2w | | 5x^2-9x+c=0 | | 2.25x^2-4x-1=0 | | n+(-21)=-14 | | n+18=15 | | (2x-3)(4y-6)= | | (x-5)(y-3)= | | 4/5*x-7/10*x=4 | | 5k^2+17k-22=0 | | (x-3)(y+6)= | | 4/15/5/7 | | -1/2x-2=0 | | P=5Q+7 | | 4x^2+19x-23=0 | | (x+2)(y+4)= | | X-94=-5x+2 | | X^4-10x-50=0 | | Y-C=S | | .5x=197125 | | .05x=197125 |